Selective depressive effect of sodium fluorosilicate on calcite during scheelite flotation. (15th January 2019) - Dong, Liuyang; Jiao, Fen; Qin, Wenqing; Zhu, Hailing; Jia, Wenhao
Highlights: SFS can chemically adsorb on calcite surface. SFS has excellent depressive effect on flotation of calcite. Flotation separation of scheelite from calcite can be achieved with SFS. An adsorption model is finally obtained. Abstract: In flotation, it is very difficult to separate scheelite from calcite. In this study, sodium fluorosilicate (SFS) was used as a depressant in the flotation separation of scheelite from calcite. The selective depression effect of the SFS on calcite was proven by corresponding experiments, such as zeta potential test, FTIR analysis and XPS analysis. The micro-flotation experiments showed that the floatability of calcite decreased sharply from 90.1% to 28.7% in the presence of SFS, while the floatability of scheelite remains high (recovery 78.2%) at pH 9.5. An efficient flotation separation between scheelite and calcite was demonstrated using artificial mixed mineral sample. Zeta potential analysis and solution chemistry calculation showed that the negatively charged species (F −, Si(OH)2 2−, SiF6 2−, and SiO(OH)3 − ) in the SFS solution were more likely to adsorb on the surface of the calcite with positive potential. XPS analysis further indicated that related chemical chelating reactions occurred between these negatively charged species and the calcium species on calcite surface, and generated CaSiO3, CaF2, CaSiF6, etc. This altered the chemical state of elements on the calcite surface. FTIR analysis also demonstrated that the chemisorption of the SFS occurred on calcite surface. These experiments together demonstrated the selective adsorption behavior of SFS on the calcite surface.